2021
DOI: 10.1038/s41370-021-00348-y
|View full text |Cite
|
Sign up to set email alerts
|

Maternal exposure to polycyclic aromatic hydrocarbons in South Texas, evaluation of silicone wristbands as personal passive samplers

Abstract: Background Prenatal exposure to polycyclic aromatic hydrocarbons (PAHs) is associated with adverse health effects in children. Valid exposure assessment methods with accurate spatial and temporal resolution across pregnancy is a critical need for advancing environmental health studies. Objective The objective of this study was to quantify maternal PAH exposure in pregnant women residing in McAllen, Texas where the prematurity rate and childhood asthma prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…One study reported moderate to strong correlations between wristband and active air sampler concentrations for a majority of the PAHs evaluated ( Dixon et al, 2018 ). In contrast, other studies reported no statistically significant correlations between wristband and active air sampler concentrations of PAHs ( Wang et al, 2019 ; Mendoza-Sanchez et al, 2021 ).…”
Section: Comparison To Other Exposure Assessment Toolsmentioning
confidence: 63%
See 2 more Smart Citations
“…One study reported moderate to strong correlations between wristband and active air sampler concentrations for a majority of the PAHs evaluated ( Dixon et al, 2018 ). In contrast, other studies reported no statistically significant correlations between wristband and active air sampler concentrations of PAHs ( Wang et al, 2019 ; Mendoza-Sanchez et al, 2021 ).…”
Section: Comparison To Other Exposure Assessment Toolsmentioning
confidence: 63%
“…The pump draws air through a filter where particle-associated chemicals are captured before reaching a sorbent. Sorbents used in comparison to silicone wristbands include a polyurethane foam (PUF) cartridge ( Dixon et al, 2018 ) and XAD-2 cartridges ( Mendoza-Sanchez et al, 2021 ). Wristbands have also been compared to OSHA versatile sampler (OVS) cartridges which contained both PUF and XAD-2 components ( Wang et al, 2019 ; Nguyen et al, 2020 ).…”
Section: Comparison To Other Exposure Assessment Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that if the concentration of an analyte is known from one sampler, the concentration that will be obtained from the other sampler can be predicted by correlation studies. Another comparative study for active and passive samplers was conducted by Itza et al In this study, participants wore wristbands and carried an active sampler with a PTFE filter and XAD tubes for 24 h [15].Based on the study results obtained from GC-MS, and as can be expected, each type of sampler provided different limits of quantifications. For instance, the limit of quantifications (LOQs) of PTFE filters were in a range from 0.01 to 0.38 ng/m 3 , for XAD adsorbent were in a range from 0.01 to 10.93 ng/m 3 , and passive samplers were from 0.03 to 56.85 ng/wristband.…”
Section: Air Sampling With Wearable Extractive Devicesmentioning
confidence: 92%
“…Previous studies reported that urinary levels of black carbon strongly differ from one street to another, as a function to the distance from to a main road [16]. Personal passive samplers will also be helpful to improve estimation of individual exposure to air pollutants [17]. Difficulties to correctly address air pollution exposure have been highlighted in previous studies.…”
Section: Exposure To Air Pollution On Covid-19 Mortalitymentioning
confidence: 99%